광 조건에 따른 식물공장 재배 쌈 배추의 기능성 성분 변화 - 정선옥(Sun-Ok Chung); 김연미(Yun-Mi Kim); 류동기(Dong-Gi Ryu); 김선주(Sun-Ju Kim); 박종태(Jong-Tae Park) (한국식품과학회지, 2014)
A recently developed Chinese cabbage cultivar, Shinhong Ssam, was cultured under different light conditions at a plant factory to evaluate effects of light on the production of functional compounds. The effects of the following combinations of red (R), blue (B), and white (W) LED light were compared to that of fluorescent light: R+B, R+W, and R+B+W. Under R+B light, the Chinese cabbage failed to grow well. In contrast, under R+W, R+B+W, and fluorescent light conditions, cabbages had similar growth rates. Cyanidin, the only anthocyanidin detected, accumulated in cabbages under LED conditions to levels more than 2-fold of that in cabbages grown under fluorescent light. Phenolic acid and flavonol levels varied subtly, whereas caffeic acid was found to be between 70- and 160-fold greater in LED-illuminated cabbages than in those exposed to fluorescent light. The amounts of free amino acids and sugars that affect the taste of vegetables were greater in the cabbages exposed to LED light than in those grown under fluorescent light conditions. In conclusion, R+W LED light produced Shinhong Ssam with greater nutritional value than those grown under R+B+W LED and fluorescent lights. 최근 육종되어 시장에 소개된 신홍쌈 배추를 다양한 광 조건의 식물공장에서 재배하여 그 영양적 특성, 특히 기능성 물질인 phenolic compounds류의 함량을 중심으로 비교분석을 수행하였다. LED 광원을 이용하였으며 LED는 적+청, 적+백, 적+청+백 세가지 조합으로 신홍쌈 재배에 사용하였고 형광등을 광원으로 이용하여 재배한 경우와 비교하였다. LED 적+청 조건에서는 배추가 정상적으로 성장하지 못하여 성분 분석연구에 사용하지 않았으며 형광등을 포함한 다른 광 조건에서는 서로 유사한 성장속도를 보였으며 정상적인 형태 및 크기로 성장하였다. Anthocyanidin 중에서는 cyanidin만이 배추 내에 축적되었으며 그 함량은 LED 조건이 형광등에 비하여 2배 이상 높은 것으로 나타났다. Phenolic acid와 flavonol의 총 함량은 광 조건에 따른 차이가 크게 나타나지 않았다. 특이하게도 caffeic acid는 형광등 조건에서는 거의 축적되지 않았으나 LED 광에서는 형광등 재배 배추에 비하여 70-160배 이상의 높은 함량을 나타내었다. 유리 아미노산과 유리당의 전체 함량은 대체로 LED 광 조건에서 높게 측정되었으나 그 차이는 크지 않았다. 결론적으로, LED 광 중 R+W 조합이 신홍쌈의 기능성 성분 축적 및 식품적 가치상승에 가장 유리한 것으로 나타났다.